Effectiveness of interventions to enhance healing of chronic foot ulcers in diabetes: a systematic review. (16th March 2020) - Vas, Prashanth; Rayman, Gerry; Dhatariya, Ketan; Driver, Vickie; Hartemann, Agnes; Londahl, Magnus; Piaggesi, Alberto; Apelqvist, Jan; Attinger, Chris; Game, Fran
Abstract: The management of diabetic foot ulcers (DFU) remains a challenge, and there is continuing uncertainty concerning optimal approaches to wound healing. The International Working Group of the Diabetic Foot (IWGDF) working group on wound healing has previously published systematic reviews of the evidence in 2008, 2012 and 2016 to inform protocols for routine care and to highlight areas which should be considered for further study. The working group has now updated this review by considering papers on the interventions to improve the healing of DFU's published between June 2014 and August 2018. Methodological quality of selected studies was independently assessed by a minimum of two reviewers using the recently published 21‐point questionnaire as recommended by IWGDF/European Wound Management Association, as well as the previously incorporated Scottish Intercollegiate Guidelines Network criteria. Of the 2275 papers identified, 97 were finally selected for grading following full text review. Overall, there has been an improvement in study design and a significant rise in the number of published studies. While previous systematic reviews did not find any evidence to justify the use of newer therapies, except for negative pressure wound therapy in post‐surgical wounds, in this review we found additional evidence to support some interventions including a sucrose‐octasulfate dressing, the combined leucocyte, fibrin and platelet patch as well as topical application of some placental membrane products, all when used in addition to usual best care. Nonetheless, the assessment and comparison of published trials remains difficult with marked clinical heterogeneity between studies: in patient selection, study duration, standard of usual care provision and the timing and description of the clinical endpoints.